Leishmaniasis General Aspects of a Stigmatized Disease - de Azevedo Calderonon, Leonardo (IntechOpen, 2022)
Leishmaniasis is a major global health challenge, affecting approximately 12 million of the poorest people in 100 countries. It is a deforming and fatal disease in the visceral form. Therapies for leishmaniasis are numerically restricted, basically consisting of the administration of miltefosine, pentavalent antimonials, amphotericin B, or pentamidine. This is an important vulnerability against therapy efficiency that must be overcome by the scientific community. This book discusses important aspects of the disease, such as treatment, epidemiology, and molecular and cell biology. The information contained herein is important for young researchers as they seek to develop safe and effective treatments for this neglected tropical disease.